SWEARING SPEECH IN THE COMMENTS COLUMN AT @JAKARTAKERAS - Koebanu, Sabri; Hardiana, Maulida (PT. Hafasy Dwi Nawasena, 2024)
Swear words on social media are increasingly widespread, many netizens are issuing swear words on anyone's Instagram account, including this @jakartakeras Instagram account. This study aims to describe swear words on the Instagram account @jakartakeras. This study examines the utterances of swear words into several forms and models of the swear words. This research is a qualitative descriptive study. The subject of this study is the comment column on the Instagram account @jakartakeras. The object of this research is to study swear words into several categories. The technique used to collect data in this study used the techniques simak bebas libat cakap. Advanced techniques used to collect data then use screenshot techniques or screenshots. Then use note-taking techniques to record swear words in the comments column of the Instagram account @jakartakeras. The method used in this study uses the padan method. then using the technique of sorting out the determining elements of the speech of Instagram users which contain swear words divided based on the shape and model of the swear words. Then the agih method is used with the direct element division technique to divide the forms of swear words based on their grammatical. Based on the research that has been analyzed, the results in this study are, swear speech is divided into seven categories or forms, namely first lexical swear words of animals, second genitals, third physical or mental state of a person, fourth object, five spirits, six professions, and seven sexual activities.